2019
DOI: 10.1126/sciadv.aax1325
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh thermal isolation across heterogeneously layered two-dimensional materials

Abstract: Heterogeneous integration of nanomaterials has enabled advanced electronics and photonics applications. However, similar progress has been challenging for thermal applications, in part due to shorter wavelengths of heat carriers (phonons) compared to electrons and photons. Here, we demonstrate unusually high thermal isolation across ultrathin heterostructures, achieved by layering atomically thin two-dimensional (2D) materials. We realize artificial stacks of monolayer graphene, MoS2, and WSe2 with thermal res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(115 citation statements)
references
References 56 publications
8
102
0
2
Order By: Relevance
“…For example, Yalon et al158a determined the thermal boundary resistance of MoS 2 on SiO 2 /Si substrate by Raman spectroscopy and validated the uniformity of temperature distribution of MoS 2 by SThM, as shown in Figure c. Similarly, SThM confirmed the temperature uniformity on artificially stacked graphene, MoS 2 and WSe 2 thin film devices which were discovered to possess ultrahigh thermal isolation . When studying MoS 2 /WS 2 lateral heterojunctions and single layer MoS 2 grain boundaries using SThM, Yasaei et al observed nonuniform heating at MoS 2 grain boundaries that indicated nonuniform current flow across them.…”
Section: Applicationsmentioning
confidence: 90%
“…For example, Yalon et al158a determined the thermal boundary resistance of MoS 2 on SiO 2 /Si substrate by Raman spectroscopy and validated the uniformity of temperature distribution of MoS 2 by SThM, as shown in Figure c. Similarly, SThM confirmed the temperature uniformity on artificially stacked graphene, MoS 2 and WSe 2 thin film devices which were discovered to possess ultrahigh thermal isolation . When studying MoS 2 /WS 2 lateral heterojunctions and single layer MoS 2 grain boundaries using SThM, Yasaei et al observed nonuniform heating at MoS 2 grain boundaries that indicated nonuniform current flow across them.…”
Section: Applicationsmentioning
confidence: 90%
“…[ 78 ] The crossplane thermal conductance, however, exhibits a more complex behavior, as it is sensitive to both in‐plane and crossplane strain. [ 79 ] Van der Waals heterostructure stacking allows one to realize an ultrahigh thermal resistance through the mismatch of mass density and phonon density in 2D materials, [ 80 ] thus having potential applications in the field of thermal isolation. It is also worth noting that suspended defect‐free membranes have higher in‐plane thermal conductivities, as the attachment to substrates and the existence of defects can strongly weaken thermal conductance due to phonon scattering.…”
Section: Fundamental Properties Of 2d Materials Beyond Graphenementioning
confidence: 99%
“…The Joule heat flux transferred across the heterojunction and the temperatures of both the graphene and hBN layers were simultaneously measured from the Raman spectrum ( Fig. 12 (a)), from which the thermal boundary conductance (TBC) between graphene and hBN was determined to be 7.4 MW/m 2 K. Vaziri et al [214] combined the Joule heating and the Raman thermometry to measure the thermal conductance of more complicated heterostructure devices involving graphene (Gr), MoS2, and WSe2 (Fig. 12 (c)).…”
Section: Cross-plane Transport: Solid-state Thermionic Structurementioning
confidence: 99%
“…(d) Measured room-temperature TBC values of 2D/2D and 2D/3D (with SiO2) interfaces and the calculated product of phonon DOS, phonon transmission, and df/dT, normalized to the minimum achieved for Gr/WSe2. (c) and (d) are adapted from [214].…”
Section: Cross-plane Transport: Solid-state Thermionic Structurementioning
confidence: 99%